China Ambition Through Digital Silk Road and Its Impact to Indonesia - Hizra Marisa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Focusing on the Digital Silk Road (DSR) initiative, this study analyzes the China's ambition through DSR and its impact to Indonesia, particularly in developing digital connectivity in Indonesia. DSR is often viewed as China's strategy to expand geopolitical influence and strengthen its authoritarian governance model through collaboration in the digital field. This study uses the theory of cooperation and cyber diplomacy as an analytical framework to understand the dynamics of this bilateral relationship. Through this theoretical lens, it will examine how China, with its ambition to become a